RETRACTED: Palmitic Acid Impedes Extravillous Trophoblast Activity by Increasing MRP1 Expression and Function - Yunali Ashar; Qiuxu Teng; John N. D. Wurpel; Zhe-Sheng Chen; Sandra E. Reznik (Biomolecules)
Normal function of placental extravillous trophoblasts (EVTs), which are responsible for uteroplacental vascular remodeling, is critical for adequate delivery of oxygen and nutrients to the developing fetus and normal fetal programming. Proliferation and invasion of spiral arteries by EVTs depends upon adequate levels of folate. Multidrug resistance-associated protein 1 (MRP1), which is an efflux transporter, is known to remove folate from these cells. We hypothesized that palmitic acid increases MRP1-mediated folate removal from EVTs, thereby interfering with EVTs’ role in early placental vascular remodeling. HTR-8/SVneo and Swan-71 cells, first trimester human EVTs, were grown in the absence or presence of 0.5 mM and 0.7 mM palmitic acid, respectively, for 72 h. Palmitic acid increased ABCC1 gene expression and MRP1 protein expression in both cell lines. The rate of folate efflux from the cells into the media increased with a decrease in migration and invasion functions in the cultured cells. Treatment with N-acetylcysteine (NAC) prevented the palmitic acid-mediated upregulation of MRP1 and restored invasion and migration in the EVTs. Finally, in an ABCC1 knockout subline of Swan-71 cells, there was a significant increase in invasion and migration functions. The novel finding in this study that palmitic acid increases MRP1-mediated folate efflux provides a missing link that helps to explain how maternal consumption of saturated fatty acids compromises the in utero environment.